Examining the impact of dance/movement therapy on empathy, peer relationships, and cultural self-efficacy in middle school: A mixed methods study - Nalini Prakash; Sherry Goodill; Suruchi Sood; Daniel T. Vader; Reneé H. Moore; Nancy Beardall; Minjung Shim (Social Sciences and Humanities Open)
Despite efforts to promote inclusivity in schools, ethnic bullying is a pervasive issue. Recent studies have highlighted the potential of empathy and cultural self efficacy within cross-cultural friendships to mitigate ethnic bullying. Violence prevention programs in the United States rely on didactic approaches and few include embodied approaches. Our goal was to examine the impact of dance/movement therapy (DMT) on empathy, peer relationships, and cultural self-efficacy among racially/ethnically diverse groups of middle school students using a mixed methods research design. Quantitative data did not demonstrate significant change in empathy, peer relationships, and cultural self-efficacy. Qualitative data described an increase in participants’ emotional intelligence including empathy, cultural self-efficacy, and positive cross-cultural relationships. Additional research is needed to determine the definitive impact of DMT on these outcomes.